SO080NOVEL EVIDENCE OF THE "PULMO-RENAL INTERACTION" AS A DISEASE DRIVER IN PATIENTS WITH CKD AND COPD. (6th June 2020) - Schunk, Stefan; Beisswenger, Christoph; Herr, Christian; Ritzmann, Felix; Sarah, Triem; Schmit, David; Omlor, Albert; Jörres, Rudolf; Watz, Henrik; Welte, Tobias; Vogelmeier, Claus; Zewinger, Stephen; et al.
Abstract: Background and Aims: Chronic kidney disease (CKD) and chronic obstructive pulmonary disease (COPD) represent a global public health problem worldwide. As such, both conditions are associated with high disease-related morbidity and mortality. However, it is unclear whether the presence of CKD aggravates the clinical course of COPD and vice versa. Method: In a novel murine model of cigarette smoke (CS)-induced lung injury combined with an adenine nephropathy model, kidney and lung inflammation, and fibrosis were studied. Moreover, in 2, 314 patients with stable COPD enrolled in the prospective, multi-centre COSYCONET study, urinary Dickkopf-3 (DKK3), a biomarker of kidney injury and CKD progression was quantified. The association between urinary DKK3 and trajectories of forced expiratory pressure in 1 second (FEV1) and estimated glomerular filtration rate (eGFR) during a median follow-up of 37.1 months, exercise capacity, risk of exacerbation, and mortality was determined. Results: In the CKD-COPD animal model, the presence of kidney injury was associated with increased systemic and pulmonary inflammation, impaired pulmonary function, as well as more severe damage of the lung architecture. Moreover, CS enhanced kidney fibrosis. Accordingly, in the COPD patients from the COSYCONET study, higher urinary DKK3 was associated with declining FEV1 during follow-up (OR 3.36, 95% CI 2.22-5.08). Moreover, high urinary DKK3 was associated with higher risk for exacerbation (OR 1.24, 95% CI 1.03-1.50), lower 6-minute walking distance, and higher all-cause mortality (HR 1.49, 95% CI 1.08-2.05). Importantly, high urinary DKK3 was associated with declining eGFR during follow-up (OR 2.23, 95% CI 1.22-4.07) independently from baseline kidney function and proteinuria, which was confirmed by a machine learning approach. Conclusion: These data uncover a novel pathophysiological link between CKD and COPD. Patient with COPD and concomitant CKD are at high risk for worsening pulmonary function and adverse outcomes. Elevated urinary DKK3 allows identification of COPD patients with progressive CKD. Measurement of urinary DKK3 in patients with COPD may therefore represent a novel tool for risk stratification and the identification of patients, who might in particular benefit from preventive therapeutic strategies to prevent progression of COPD and CKD as well.